Clinical Characteristics and Long-Term Recombinant Human Growth Hormone Treatment of 18q- Syndrome: A Case Report and Literature Review - Liu, Shanshan; Chen, Meiping; Yang, Hongbo; Chen, Shi; Wang, Linjie; Duan, Lian; Zhu, Huijuan; Pan, Hui (Frontiers in Endocrinology, 2021)
Abstract Background:18q- syndrome is a rare chromosomal disease caused by deletion of the long arm of chromosome 18. Some cases with 18q- syndrome can be combined with growth hormone deficiency (GHD) but data on the efficacy of recombinant human growth hormone (rhGH) treatment in 18q- syndrome are limited. Methods：Here we report one case of 18q- syndrome successfully treated with long-term rhGH supplement. Previously reported cases in the literature are also reviewed to investigate the karyotype-phenotype relationship and their therapeutic response to rhGH . Results: A 7.9-year-old girl was referred for evaluation for short stature. Physical exam revealed proportionally short stature with a height of 111.1 cm (-3.02 SDS), low-set ears, high-arched palate, small jaw, web-neck, widely spaced nipples, long and tapering fingers and cubitus valgus. Thyroid function test indicated hypothyroidism. Peak value of growth hormone was 10.26 ng/ml in levodopa provocation test. Insulin-like growth factor 1 (IGF-1) was 126 ng/ml. Other laboratory investigations, including complete blood cell count, liver and kidney function, gonadal function, serum adrenocorticotropin levels and serum cortisol levels, were all within normal ranges. Karyotype analysis showed 46, XX, del (18) (q21). L-thyroxine replacement and rhGH treatment were initiated and maintained in the following 7 years. At the age of 14.8, her height has reached 159.5cm with a height SDS increase of 2.82 SDS (from -3.02 SDS to -0.20 SDS). No significant side effects were found during the treatment. Literature review indicated the average rhGH treatment duration of 16 patients was 5.9±3.3 years, and the average height SDS significantly increased from -3.12±0.94 SDS to -1.34±1.16 SDS after rhGH treatment (p＜0.0001) . Conclusion: The main clinical manifestations of 18q- syndrome include characteristic appearance, intellectual disability, and abnormal genital development. The literature review suggested a significant height benefit for short stature with 18q- syndrome from long-term rhGH treatment.